Force and statecraft : diplomatic challenges of our time - Lauren, Paul Gordon; Craig, Gordon Alexander, 1913-2005.; George, Alexander L. (New York : Oxford University Press, 2021)
"Uniquely combining history, political science, and international law, this classic, timely and concise resource provides a historical discussion and insightful analysis of diplomacy"
Introduction -- PART 1. FROM THE PAST TO THE PRESENT. Chapter 1: The Emergence of Diplomacy and the Great Powers -- Chapter 2: The Classical System of Diplomacy, 1815-1914 -- Chapter 3: The Diplomatic Revolution Begins, 1919-1939 -- Chapter 4: A Postwar System of Security: Great Power Directorate or United Nations? -- Chapter 5: The Cold War -- Chapter 6: The Evolving International System -- PART 2. HISTORY, THEORY, AND PRACTICE. Chapter 7: Lessons of History and Knowledge for Statecraft -- Chapter 8: Negotiation -- Chapter 9: Deterrence -- Chapter 10: Coercive Diplomacy -- Chapter 11: Crisis Management -- PART 3. RESTRAINTS AND REFLECTIONS. Chapter 12: Ethics and Other Restraints on Force and Statecraft -- Conclusion: Reflections on Force and Statecraft and the Challenges of Our Time.
Includes bibliographical references and index.
Keywords: World politics -- 19th century; World politics -- 20th century; World politics -- 21st century; Diplomacy